2008
DOI: 10.1007/s10792-008-9221-7
|View full text |Cite
|
Sign up to set email alerts
|

Intensified monitoring of circadian blood pressure and heart rate before and after intravitreous injection of bevacizumab: preliminary findings of a pilot study

Abstract: Before the intravitreal injection, BP values were increased in the majority of the patients. The elevated BP load might be related to probable pre-injection stressors. There seems to be no general rise in mean BP, heart rate and pulse pressure after intravitreal bevacizumab, although a decrease in serum VEGF-A can occur in individual patients. The reduced nocturnal dipping could be caused by pharmacodynamic effects on the vasal tone; this preliminary but striking finding warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 45 publications
0
15
0
1
Order By: Relevance
“…17 The pharmacokinetic data of serum concentration of bevacizumab after intravitreal injection from two hypertensive patients were reported, and peak serum levels of bevacizumab were 86.5 and 59.8 ng/ml at post-injection hours 120 and 168, respectively. 18 Taken these together, the increase in the 30-min systolic BP values was probably not because of the adverse effects of anti-VEGF therapy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…17 The pharmacokinetic data of serum concentration of bevacizumab after intravitreal injection from two hypertensive patients were reported, and peak serum levels of bevacizumab were 86.5 and 59.8 ng/ml at post-injection hours 120 and 168, respectively. 18 Taken these together, the increase in the 30-min systolic BP values was probably not because of the adverse effects of anti-VEGF therapy.…”
Section: Discussionmentioning
confidence: 93%
“…Importantly, our results are similar to those of an earlier study using devices for automatic 24-h recording of circadian BP after intravitreal bevacizumab injection. 18 BP shows high intra-and interindividual variability, as well as diurnal changes. 19 In this study, baseline measurements were taken 1-2 h before the procedure, and follow-up examinations were performed in the afternoon, to minimize the effect of diurnal variation on BP.…”
Section: Discussionmentioning
confidence: 99%
“…As much as 30% of an intravitreal dose of bevacizumab was recovered in the systemic circulation in animal models [59]. Intravitreal bevacizumab has also been associated with sustained decrease of serum VEGF levels in adults with age-related macular degeneration [60,61] and proliferative diabetic retinopathy [62][63][64]. More recently, bevacizumab has been shown to reduce serum VEGF concentrations in human infants with ROP following intravitreal administration -an effect that has been demonstrated to persist for 2 months in patients with type 1 disease [65][66][67].…”
Section: Safetymentioning
confidence: 99%
“…Decreased VEGF levels in human plasma or serum have also been reported after the injection of intravitreal bevacizumab. Ziemssen and colleagues 14 showed a reduction in serum VEGF 1 day and 1 week after treatment of AMD in several patients. This finding was consistent with the increased serum bevacizumab levels they detected at these times.…”
mentioning
confidence: 97%
“…11,12 After observing fellow eye effects and the sensitivity of preretinal neovascularization to anti-VEGF agents, I proposed the use of lower doses of bevacizumab or changing to ranibizumab when treating ROP to lower the systemic risk in this susceptible population. 13 Subsequently, several investigators 14,15 have confirmed the presence of bevacizumab in the serum after intravitreal injection; however, the assays for bevacizumab in human serum are technically challenging because of the presence of other human IgG. Decreased VEGF levels in human plasma or serum have also been reported after the injection of intravitreal bevacizumab.…”
mentioning
confidence: 99%